Carbon foil-coated conductive paste and preparation method thereof

By improving the components, ratio and process of the conductive paste of lithium batteries, the emulsification and multi-block copolymerization method are used to modify the acrylic resin, combined with the assembly of conductive polymers, the compatibility and electrochemical stability problems in the preparation process of conductive paste are solved, and the cycle life and comprehensive performance of lithium batteries are significantly improved.

CN119852406AInactive Publication Date: 2025-04-18合肥源元科技股份有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510054283.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation process, the conductive paste of existing lithium batteries has problems with polymer materials, phase separation and electrochemical stability, which leads to precipitation of additives and affects the cycle life and consistency of lithium batteries. At the same time, the existing adhesives do not have electronic conductivity, which increases the resistance performance of the carbon coating layer.

Method used

By synchronous improvement of components, ratios and processes, the chemical structure of the acrylic resin is modified by emulsification, multi-block, random copolymerization methods, and modified resins with bonding, dispersion and crosslinking functions are synthesized, and the conductive polymer is added for assembly to improve conductivity and compatibility.

Benefits of technology

It significantly improves the adhesion of the coating, solvent resistance and electrolyte resistance, improves the cycle life, capacity retention and comprehensive performance of lithium batteries, and reduces the dependence on additives and the use of organic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852406A_ABST
    Figure CN119852406A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic paste, in particular to carbon-foil-coated conductive paste and a preparation method thereof.The carbon-foil-coated conductive paste is composed of a conductive agent, a modified acrylic acid composite resin emulsion and a solvent; the weight part ratio of the conductive agent to the modified acrylic acid composite resin emulsion to the solvent is (5-30): (10-60): (40-100). By synchronously improving the components, the proportion and the process, modifying by adopting an emulsification and multi-component copolymerization method and controlling the reaction process, the chemical structure and the molecular structure of the acrylic resin are synchronously adjusted and changed, a random copolymerization and block copolymerization polymer is generated, the emulsifying, dispersing and homogenizing effects are good, the polymer can be directly applied to preparation of conductive paste, and the application range is wide. According to the present invention, the prepared adhesive can provide dispersion, adhesion and cross-linking effects, has no compatibility problem, does not require the additional use of a dispersant, a thickener, a cross-linking agent, a defoaming agent and other auxiliary agents, reduces the use amount of the organic solvent, and is environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic pastes, in particular to a carbon foil-coated conductive paste and a preparation method thereof. Background Art

[0002] As a new energy power form with development potential, lithium batteries have put forward increasingly urgent requirements for improving their comprehensive performance in the fields of power and energy storage batteries. Among them, battery consistency, cycle life, safety performance and rate performance are particularly critical. Among these performance improvement strategies, carbon-coated foil technology stands out. Carbon-coated foil, that is, foil with a conductive coating on the surface, can significantly reduce the contact resistance between the positive and negative electrode materials and the current collector, effectively curb the growth of dynamic internal resistance during the cycle, enhance the adhesion between the positive and negative electrode materials and the current collector, and reduce the amount of binder used when coating the positive and negative electrode materials. This series of advantages has significantly improved the battery's gram capacity, cycle life, safety performance and rate performance.

[0003] At present, the conductive paste for carbon foil coating is mainly composed of an aqueous system consisting of a conductive agent, a binder, a dispersant, a thickener, an additive and a solvent. It is applied to the surface of aluminum foil or copper foil, and the moisture is removed by heating to make the binder cross-linked to form a film, thereby firmly fixing the conductive particles on the surface of the foil. In addition, in order to improve the density and bonding strength of the coating, some conductive pastes will also add a cross-linking agent. However, in actual production, chelating agents, defoaming agents, preservatives and other additives are also needed. Although these additives are helpful in the preparation process of the conductive coating, there is a problem that the electrolyte (carbonate solvent) is easily precipitated after long-term immersion during battery use, resulting in a decrease in coating adhesion and adverse effects on internal systems such as the electrolyte.

[0004] More importantly, the high molecular (polymer) components in existing conductive pastes do not have electronic conductivity. When they are covered on the surface of conductive carbon materials such as carbon black, graphite, and carbon nanotubes, they will form electron channel blocking points, reduce the number of electron channels, and increase resistance.

[0005] In addition, please refer to the Chinese invention patent application number 202111395159.4, which discloses a water-based binder for lithium-ion batteries. The binder is composed of a composite of poly (3,4-ethylenedioxyphene) monomer: polystyrene sulfonate (PEDOT:PSS) and polyacrylic acid (PAA). It combines the high conductivity of PEDOT:PSS with the strong adhesion and elasticity of PAA. PEDOT:PSS and PAA are formed into a composite binder PEDOT:PSS-PAA through high-energy ball milling. The electrochemical performance is more significantly optimized and the preparation method is simple. However, PAA and PEDOT:PSS are physically blended, which poses the risk of polymer compatibility and phase separation, and the performance is not stable.

[0006] In summary, in the preparation process of conductive paste in the existing technology, special binders need to be used and a variety of additives need to be added. This not only brings about problems such as compatibility, phase separation and electrochemical stability of polymer materials, but may also cause precipitation of additives, affecting key performance of lithium batteries such as cycle life and consistency. At the same time, the existing adhesives do not have electronic conductivity, which increases the resistance performance of the carbon coating layer. Therefore, the existing technology cannot meet the urgent need to improve the comprehensive performance of lithium batteries. Summary of the Invention

[0007] The object of the present invention is to provide a carbon foil-coated conductive paste and a preparation method thereof. By simultaneously improving the components, proportions and processes, using emulsification, multi-block and random copolymerization methods for modification, and controlling the reaction process to achieve simultaneous changes in the chemical structure of the acrylic resin, a resin with multiple functions such as bonding and dispersion and cross-linking functional groups is synthesized based on acrylic acid. At the same time, the conductivity is improved by adding a conductive polymer for assembly and adaptation, thereby enhancing the interaction between polymer materials and effectively solving the technical problems raised in the above-mentioned background technology.

[0008] To achieve the above objectives, the present invention provides the following technical solutions.

[0009] A carbon foil-coated conductive paste comprises a conductive agent, a modified acrylic composite resin emulsion, and a solvent. The weight ratio of the components is conductive agent: modified acrylic composite resin emulsion: solvent = (5-30): (10-60): (40-100). In addition, a polyisocyanate crosslinking agent can be added later for crosslinking as needed. Under the action of the additional isocyanate crosslinking agent, chain segments in the modified acrylic composite resin emulsion are crosslinked to form a dense three-dimensional network structure, thereby significantly improving the adhesion, solvent resistance, and electrolyte resistance of the coating.

[0010] Preferably, the modified acrylic composite resin emulsion is prepared by polymerization of acrylic monomers and hydroxyl-containing styrene monomers;

[0011] The molar ratio of acrylic acid monomer to hydroxyl styrene monomer is (30-60):

[0012] (10-20).

[0013] Preferably, the acrylic monomer is at least one of acrylic acid, methacrylic acid, ethacrylic acid, and propylacrylic acid.

[0014] Preferably, the hydroxyl-containing styrene monomer is at least one of (4-vinylphenyl)methanol, 2-(4-vinylphenyl)ethanol, and 3-(4-vinylphenyl)propanol.

[0015] Preferably, the specific preparation method of the modified acrylic composite resin emulsion is as follows:

[0016] Step 1: Weighing an acrylic monomer and a hydroxyl styrene monomer in a molar ratio of (30-60): (10-20), dissolving the acrylic monomer, hydroxyl styrene monomer, S-1-dodecyl-S`-(α,α`-dimethyl-α-acetic acid) trithiocarbonate (MTTCD), and azobisisobutyronitrile in ethanol in a certain ratio, generally monomer: chain transfer agent: initiator = 100:1:0.5, adding them to a reactor and dissolving them completely, slowly passing nitrogen at room temperature for 30 minutes to remove oxygen in the system, raising the reaction temperature to 75°C, reacting under nitrogen protection for a certain time, washing the reaction solution with petroleum ether, and drying the precipitate to obtain a random copolymer;

[0017] Step 2: The random copolymer obtained in step 1, styrene sulfonic acid, and azobisisobutyronitrile are dissolved in ethanol in a certain ratio, generally monomer: chain transfer agent: initiator = 10:1:0.1, added to the reactor and completely dissolved, and then slowly nitrogen is passed through the system for 30 minutes at room temperature to remove oxygen, and the reaction temperature is raised to 75°C, and the reaction is carried out under nitrogen protection for a certain time, and the reaction liquid is washed with petroleum ether, and the precipitate is dried to obtain a random copolymer-block polymer;

[0018] Step 3: Dissolve the random copolymer-block polymer solution obtained in step 2 in ionized water, and then alkalize and ionize it with sodium bicarbonate to adjust the pH to 3 to 11, preferably 7, to obtain an ionized resin emulsion;

[0019] Step 4: Stir and mix the ionized resin emulsion obtained in step 3 with 5% PSS:PEDOT liquid of corresponding pH to form a polyacrylic acid-polythiophene resin emulsion and obtain a modified acrylic composite resin emulsion, wherein PSS:PEDOT is consistent with that in the Chinese invention patent application number 202111395159.4.

[0020] Preferably, the conductive agent is any one or more mixtures of carbon black, graphite, carbon fiber, carbon tube, and graphene.

[0021] Preferably, the solvent is any one or more mixtures of deionized water, ethanol, propanol, isopropanol, n-propanol, and n-butanol.

[0022] Preferably, a method for preparing a carbon foil-coated conductive paste comprises the following specific preparation steps:

[0023] Step 1: Disperse the modified acrylic composite resin emulsion into the solvent and stir until uniformly dispersed;

[0024] Step 2: Add the conductive agent and disperse for 1-4 hours at a disperser speed of 1000-4000 RPM until the surface of the conductive agent is completely wetted to obtain a dispersion;

[0025] Step 3: The dispersion obtained in step 2 is subjected to wet nano-grinding and homogenization at a grinding speed of 1000-6000 RPM and a grinding time of 1-6 hours to obtain a uniformly dispersed carbon foil-coated conductive slurry.

[0026] The carbon-coated foil conductive paste is used to prepare a functional coating for lithium-ion battery current collector metal foil to form a carbon-coated foil. In the carbon-coated foil conductive paste, the acrylic monomer in the random copolymerization of the modified acrylic composite resin emulsion can play a major role in bonding, the hydroxyl monomer can play a role in dispersing and stabilizing the conductive polymer and can serve as a reactive group for cross-linking with isocyanate groups. Among them, block sodium polystyrene sulfonate can serve as a pairing polymer of PSS:PEDOT to effectively improve the compatibility between the two.

[0027] Compared with the prior art, the present invention has the following beneficial effects.

[0028] 1. The present invention improves the components, proportions and processes simultaneously, adopts emulsification and multi-component copolymerization methods for modification, controls the reaction process to achieve simultaneous adjustment and change of the chemical structure and molecular structure of the acrylic resin, and generates random copolymerization and block copolymerization polymers. The polymers have good emulsification, dispersion and homogenization effects and can be directly used in the preparation of conductive pastes. They can play three roles of dispersion, bonding and cross-linking without compatibility issues. In addition, there is no need to use additional dispersants, thickeners, cross-linking agents, defoaming agents and other additives, and the use of organic solvents is reduced, making it more environmentally friendly.

[0029] 2. The present invention adds an isocyanate crosslinking agent to the present invention, and the chain segments in the modified acrylic composite resin emulsion are crosslinked to form a dense three-dimensional network structure, which significantly improves the adhesion, solvent resistance and electrolyte resistance of the coating.

[0030] 3. The polythiophene conductive polymer formulated with the modified acrylic composite resin emulsion provided by the present invention is beneficial for improving the conductivity and microstructural properties of the carbon foil conductive coating, reducing the internal resistance of the battery and increasing the cycle life, effectively improving the cycle life and capacity retention rate of the battery, and improving the battery's comprehensive performance such as cycle life, consistency, and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of a specific process of the preparation method of the carbon foil conductive paste provided by the present invention;

[0032] Figure 2 The figure is a schematic diagram of a specific process of the method for preparing the modified acrylic composite resin emulsion of the present invention. DETAILED DESCRIPTION

[0033] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0034] See also Figure 1 and Figure 2 The present invention provides a carbon foil-coated conductive paste, which is composed of a conductive agent, a modified acrylic composite resin emulsion, and a solvent; the weight ratio of each component is conductive agent: modified acrylic composite resin emulsion: solvent = (5-30): (10-60): (40-100). In addition, a polyisocyanate cross-linking agent can be added later for cross-linking as needed. Under the action of the additional isocyanate cross-linking agent, the chain segments in the modified acrylic composite resin emulsion are cross-linked to form a dense three-dimensional network structure, which significantly improves the adhesion, solvent resistance, and electrolyte resistance of the coating. The conductive agent is any one or more mixtures of carbon black, graphite, carbon fiber, carbon tube, and graphene; and the solvent is any one or more mixtures of deionized water, ethanol, propanol, isopropanol, n-propanol, and n-butanol.

[0035] The modified acrylic composite resin emulsion is prepared by polymerizing acrylic monomers and hydroxyl-containing styrene monomers, wherein the molar ratio of the acrylic monomers to the hydroxyl-containing styrene monomers is (30-60): (10-20).

[0036] The acrylic monomer is at least one of acrylic acid, methacrylic acid, ethacrylic acid, and propylacrylic acid.

[0037] The hydroxyl-containing styrene monomer is at least one of (4-vinylphenyl)methanol, 2-(4-vinylphenyl)ethanol, and 3-(4-vinylphenyl)propanol.

[0038] like Figure 2 As shown, the specific preparation steps of the modified acrylic composite resin emulsion are as follows;

[0039] Step 1: Weighing an acrylic monomer and a hydroxyl styrene monomer in a molar ratio of (30-60): (10-20), dissolving the acrylic monomer, hydroxyl styrene monomer, S-1-dodecyl-S`-(α,α`-dimethyl-α-acetic acid) trithiocarbonate (MTTCD), and azobisisobutyronitrile in ethanol in a certain ratio, generally monomer: chain transfer agent: initiator = 100:1:0.5, adding them to a reactor and dissolving them completely, slowly passing nitrogen at room temperature for 30 minutes to remove oxygen in the system, raising the reaction temperature to 75°C, reacting under nitrogen protection for a certain time, washing the reaction solution with petroleum ether, and drying the precipitate to obtain a random copolymer;

[0040] Step 2: The random copolymer obtained in step 1, styrene sulfonic acid, and azobisisobutyronitrile are dissolved in ethanol in a certain ratio, generally monomer: chain transfer agent: initiator = 10:1:0.1, added to the reactor and completely dissolved, and then slowly nitrogen is passed through the system for 30 minutes at room temperature to remove oxygen, and the reaction temperature is raised to 75°C, and the reaction is carried out under nitrogen protection for a certain time, and the reaction liquid is washed with petroleum ether, and the precipitate is dried to obtain a random copolymer-block polymer;

[0041] Step 3: Dissolve the random copolymer-block polymer solution obtained in step 2 in ionized water, and then alkalize and ionize it with sodium bicarbonate to adjust the pH to 3 to 11, preferably neutral, to obtain an ionized resin emulsion;

[0042] Step 4: Stir and mix the ionized resin emulsion obtained in step 3 with 5% PSS:PEDOT liquid of corresponding pH to form a polyacrylic acid-polythiophene resin emulsion and obtain a modified acrylic composite resin emulsion.

[0043] Among them, PSS:PEDOT is consistent with that in the Chinese invention patent with application number 202111395159.4.

[0044] See also Figure 1 The specific preparation steps of carbon foil conductive paste are as follows:

[0045] Step 1: Disperse the modified acrylic composite resin emulsion into the solvent and stir until uniformly dispersed;

[0046] Step 2: Add the conductive agent and disperse for 1-4 hours at a disperser speed of 1000-4000 RPM until the surface of the conductive agent is completely wetted to obtain a dispersion;

[0047] Step 3: The dispersion obtained in step 2 is subjected to wet nano-grinding and homogenization at a grinding speed of 1000-6000 RPM and a grinding time of 1-6 hours to obtain a uniformly dispersed carbon foil-coated conductive slurry.

[0048] The carbon-coated foil conductive paste is used to prepare a functional coating for lithium-ion battery current collector metal foil to form a carbon-coated foil. In the carbon-coated foil conductive paste, the acrylic monomer in the random copolymerization of the modified acrylic composite resin emulsion can play a major role in bonding, the hydroxyl monomer can play a role in dispersing and stabilizing the conductive polymer and can serve as a reactive group for cross-linking with isocyanate groups. Among them, block sodium polystyrene sulfonate can serve as a pairing polymer of PSS:PEDOT to effectively improve the compatibility between the two.

[0049] Example 1

[0050] Based on the above, this embodiment 1 provides more specific components, proportions, and preparation methods of the carbon-coated conductive paste and the modified acrylic composite resin emulsion. The preparation of the modified acrylic composite resin emulsion specifically includes the following steps:

[0051] Step 1: Weigh acrylic acid: (4-vinylphenyl)methanol: trithiocarbonate (MTTCD): azobisisobutyronitrile according to the molar ratio of 40:10:0.5:0.2, take 50 g of the prepared reactants and stir and dissolve them in 500 ml of ethanol, slowly pass nitrogen at room temperature for 30 minutes to remove oxygen in the system, raise the reaction temperature to 75°C, react under nitrogen protection, react for a certain time, wash the reaction solution with petroleum ether, and dry the precipitate;

[0052] Step 2: The polymer obtained above, 4 g of styrene sulfonic acid, and 0.4 g of azobisisobutyronitrile were dissolved in 800 ml of ethanol, added to the reactor and completely dissolved, and then nitrogen was slowly passed through the system for 30 minutes at room temperature to remove oxygen. The reaction temperature was raised to 75°C, and the reaction was carried out under nitrogen protection for a certain time. The reaction solution was washed with petroleum ether, and the precipitate was dried to obtain a random copolymer-block polymer;

[0053] Step 3: Dissolve 10 g of the obtained random copolymer-block polymer in 50 ml of deionized water, and then alkalize and ionize it with 20% sodium hydroxide until the pH value measured by the pH meter is 7, thereby obtaining a neutral resin solution;

[0054] Step 4: 100 ml of a 20% by mass neutral resin solution and 10 ml of a 5% PSS:PEDOT liquid are stirred and mixed for use to form a polyacrylic acid-polythiophene resin emulsion, and finally a modified acrylic composite resin emulsion is obtained.

[0055] The following provides the components, proportions and preparation method of the lithium battery carbon foil conductive paste further prepared by using the prepared modified acrylic composite resin emulsion, specifically:

[0056] The conductive agent of the conductive paste for lithium battery carbon foil coating is selected from nano-conductive carbon black and graphite particles, and the solvent is selected from deionized water and ethanol. The modified acrylic composite resin emulsion prepared in this example is used, and the weight ratio of conductive carbon black: graphite: polyacrylic acid-polythiophene resin solution: deionized water: isopropyl alcohol is 10:2:50:28:28 to prepare a conductive paste with good homogenization effect.

[0057] The specific preparation method is as follows: the modified acrylic composite resin emulsion prepared in this embodiment is dispersed in a mixture of deionized water and isopropyl alcohol, stirred until uniformly dispersed, conductive carbon black and graphite powder are added, and high-speed stirring and dispersion are carried out at 1000 RPM for 1 hour until the surface of the conductive agent is completely wetted to obtain a dispersion liquid, and then the dispersion liquid is wet nano-grinded and homogenized for 3 hours to obtain a water-based carbon foil-coated conductive slurry with uniform mixing and good homogenization effect.

[0058] Example 2

[0059] This embodiment 2 is based on the above embodiment 1 and provides more specific components, proportions and preparation methods of carbon foil-coated conductive paste and modified acrylic composite resin. The preparation of modified acrylic composite resin emulsion specifically includes the following steps:

[0060] Step 1: Weigh acrylic acid: 2-(4-vinylphenyl)ethanol: trithiocarbonate (MTTCD): azobisisobutyronitrile according to the molar ratio of 50:10:0.5:0.2, take 50 g of the prepared reactants and stir and dissolve them in 500 ml of ethanol, slowly pass nitrogen at room temperature for 30 minutes to remove oxygen in the system, raise the reaction temperature to 75°C, react under nitrogen protection, react for a certain time, wash the reaction solution with petroleum ether, and dry the precipitate;

[0061] Step 2: The polymer obtained above, 5 g of styrene sulfonic acid, and 0.4 g of azobisisobutyronitrile were dissolved in 800 ml of ethanol, added to the reactor and completely dissolved, and then nitrogen was slowly passed through the system for 30 minutes at room temperature to remove oxygen. The reaction temperature was raised to 75°C, and the reaction was carried out under nitrogen protection for a certain time. The reaction solution was washed with petroleum ether, and the precipitate was dried to obtain a random copolymer-block polymer;

[0062] Step 3: Dissolve 10 g of the obtained random copolymer-block polymer in 50 ml of deionized water, and then alkalize and ionize it with 20% sodium hydroxide until the pH value is finally neutral as measured by a pH meter to obtain a neutral resin solution;

[0063] Step 4: 100 ml of a 20% by mass neutral resin solution and 20 ml of a 5% PSS:PEDOT liquid are stirred and mixed for use to form a polyacrylic acid-polythiophene resin emulsion, thereby obtaining a modified acrylic composite resin emulsion.

[0064] Provided below is a method for further preparing a conductive paste for coating carbon foil on lithium batteries using the prepared modified acrylic composite resin emulsion and its preparation method.

[0065] The components, proportions, and preparation method of the conductive paste for lithium battery carbon foil coating are as follows: the conductive agent of the conductive paste for lithium battery carbon foil coating is selected from nano-conductive carbon black and graphite particles, and the solvent is selected from deionized water and ethanol. The modified acrylic composite resin emulsion prepared in this embodiment is used, and the weight ratio of conductive carbon black: carbon nanotubes: polyacrylic acid-polythiophene resin solution: deionized water: isopropyl alcohol is 10:1:50:30:30 to prepare a conductive paste with good homogenization effect.

[0066] The specific preparation method is as follows: the modified acrylic composite resin emulsion prepared in this embodiment is dispersed in a mixture of deionized water and isopropyl alcohol, and stirred until uniformly dispersed; conductive carbon black and carbon nanotube powder are added, and the mixture is stirred and dispersed at a high speed of 1000 RPM for 5 hours until the surface of the conductive agent is completely wetted to obtain a dispersion; the dispersion is subjected to wet nano-grinding and homogenization for 5 hours to obtain a water-based carbon foil-coated conductive slurry with uniform mixing and good homogenization effect.

[0067] Example 3

[0068] This Example 3, based on the above-mentioned Examples 1 and 2, provides more specific components, proportions, and preparation methods of the carbon foil-coated conductive paste and the modified acrylic composite resin. The preparation of the modified acrylic composite resin emulsion specifically includes the following steps:

[0069] Step 1: Weigh acrylic acid: 2-(4-vinylphenyl)ethanol: trithiocarbonate (MTTCD): azobisisobutyronitrile according to the molar ratio of 50:10:0.5:0.2, take 50 g of the prepared reactants and stir and dissolve them in 500 ml of ethanol, slowly pass nitrogen at room temperature for 30 minutes to remove oxygen in the system, raise the reaction temperature to 75°C, react under nitrogen protection, react for a certain time, wash the reaction solution with petroleum ether, and dry the precipitate;

[0070] Step 2: The polymer obtained above, 5 g of styrene sulfonic acid, and 0.4 g of azobisisobutyronitrile were dissolved in 800 ml of ethanol, added to the reactor and completely dissolved, and then nitrogen was slowly passed through the system for 30 minutes at room temperature to remove oxygen. The reaction temperature was raised to 75°C, and the reaction was carried out under nitrogen protection for a certain time. The reaction solution was washed with petroleum ether, and the precipitate was dried to obtain a random copolymer-block polymer;

[0071] Step 3: Dissolve 10 g of the obtained random copolymer-block polymer in 50 ml of deionized water, and then alkalize and ionize it with 20% sodium hydroxide until the pH value is finally neutral as measured by a pH meter to obtain a neutral resin solution;

[0072] Step 4: 100 ml of a 20% by mass neutral resin solution and 20 ml of a 5% PSS:PEDOT liquid are stirred and mixed for use to form a polyacrylic acid-polythiophene resin emulsion, thereby obtaining a modified acrylic composite resin emulsion.

[0073] The following provides a method for further preparing a conductive paste for coating carbon foil on lithium batteries using the prepared modified acrylic composite resin emulsion and a preparation method thereof.

[0074] The components, proportions and preparation method of the conductive paste for lithium battery carbon foil coating are as follows:

[0075] The conductive agent of the conductive paste for lithium battery carbon foil coating is selected from nano-conductive carbon black and graphite particles, and the solvent is selected from deionized water and ethanol. The modified acrylic composite resin emulsion prepared in this example is used, and the weight ratio of conductive carbon black: carbon nanotubes: polyacrylic acid-polythiophene resin solution: deionized water: n-propanol is 10:1:50:30:30 to prepare a conductive paste with good homogenization effect.

[0076] The specific preparation method is as follows: the modified acrylic composite resin emulsion prepared in this embodiment is dispersed in a mixture of deionized water and isopropyl alcohol, and stirred until uniformly dispersed; carbon nanotubes and graphene powder are added, and the mixture is stirred and dispersed at a high speed of 1000 RPM for 5 hours until the surface of the conductive agent is completely wetted to obtain a dispersion; the dispersion is subjected to wet nano-grinding and homogenization for 5 hours to obtain a water-based carbon foil-coated conductive slurry with uniform mixing and good homogenization effect.

[0077] The above embodiments of the present invention only list some of the technical solutions. Within the scope of materials, proportions, processes and parameters described in the present invention, specific selections can be made using conventional technologies, and the technical effects described in the present invention can be achieved. Therefore, they will not be listed one by one here.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A carbon foil-coated conductive slurry, characterized in that: The carbon-coated foil conductive paste is composed of a conductive agent, a modified acrylic composite resin emulsion and a solvent; The weight ratio of each component is conductive agent: modified acrylic composite resin emulsion: solvent = (5-30): (10-60): (40-100).

2. A modified acrylic composite resin emulsion according to claim 1, characterized in that: The modified acrylic composite resin emulsion is polymerized from acrylic monomers and hydroxyl-containing styrene monomers; The molar ratio of the acrylic monomer to the hydroxyl-containing styrene monomer is (30-60): (10-20).

3. The modified acrylic composite resin emulsion according to claim 2, characterized in that: The acrylic monomer is at least one of acrylic acid, methacrylic acid, ethacrylic acid, and propylacrylic acid.

4. The modified acrylic composite resin emulsion according to claim 3, characterized in that: The hydroxyl-containing styrene monomer is at least one of (4-vinylphenyl)methanol, 2-(4-vinylphenyl)ethanol and 3-(4-vinylphenyl)propanol.

5. The modified acrylic composite resin emulsion according to claim 4, characterized in that: The specific preparation method of the modified acrylic composite resin emulsion is as follows: Step 1: Weigh the acrylic monomer and the hydroxyl styrene monomer in a molar ratio of (30-60): (10-20), dissolve the acrylic monomer, hydroxyl styrene monomer, S-1-dodecyl-S`-(α, α`-dimethyl-α-acetic acid) trithiocarbonate (MTTCD), and azobisisobutyronitrile in ethanol in a certain ratio, generally monomer: chain transfer agent: initiator = 100: 1: 0.5, add to the reactor and dissolve completely, slowly pass nitrogen for 30 minutes at room temperature to remove oxygen in the system, raise the reaction temperature to 75°C, react under nitrogen protection, react for a certain time, use petroleum ether to wash the reaction solution, and dry the precipitate to obtain a random copolymer; Step 2: dissolving the random copolymer, styrene sulfonic acid and azobisisobutyronitrile obtained in step 1 in ethanol in a certain ratio, generally monomer: chain transfer agent: initiator = 10:1:0.1, adding to the reactor and dissolving completely, slowly passing nitrogen for 30 minutes at room temperature to remove oxygen in the system, raising the reaction temperature to 75°C, reacting under nitrogen protection for a certain time, washing the reaction solution with petroleum ether, and drying the precipitate to obtain a random copolymer-block polymer; Step 3: dissolving the random copolymer-block polymer solution obtained in step 2 with ionized water, and then alkalizing and ionizing with sodium bicarbonate to make the pH value finally present in a state of 3 to 11, preferably 7, to obtain an ionized resin emulsion; Step 4: Stir and mix the ionized resin emulsion obtained in step 3 with 5% PSS:PEDOT liquid of corresponding pH for standby use to form a polyacrylic acid-polythiophene resin emulsion, thereby obtaining the modified acrylic composite resin emulsion.

6. The carbon-coated foil conductive paste according to claim 1, characterized in that: The conductive agent is any one or more mixtures of carbon black, graphite, carbon fiber, carbon tube, and graphene.

7. The carbon foil-coated conductive paste according to claim 1, characterized in that: The solvent is any one or more mixtures of deionized water, ethanol, propanol, isopropanol, n-propanol and n-butanol.

8. A method for preparing a carbon foil-coated conductive slurry, characterized in that: The specific preparation steps are as follows: Step 1: dispersing the modified acrylic composite resin emulsion into a solvent and stirring until the emulsion is evenly dispersed; Step 2: Add the conductive agent and disperse for 1-4 hours at a disperser speed of 1000-4000 RPM until the surface of the conductive agent is completely wetted to obtain a dispersion; Step 3: The dispersion obtained in step 2 is subjected to wet nano-grinding and homogenization, with a grinding speed of 1000-6000 RPM and a grinding time of 1-6 hours to obtain the uniformly dispersed carbon-coated conductive slurry.

Citation Information

Patent Citations

  • A water-based binder for lithium-ion batteries and its preparation method

    CN114204026B

  • Free radical-controllable RAFT soap-free emulsion polymerization method for hydroxy acrylic resin

    CN112625198A

  • Modified acrylic resin, preparation method thereof and secondary battery carbon coating

    CN114957522A

  • Lithium battery carbon foil coating conductive paste, modified acrylic acid composite resin emulsion and preparation

    CN116462792A